PEMANFAAT FREKUENSI BUNYI MATERIAL SEBAGAI DASAR PENGUJIAN MODULUS ELASTISITAS PADA PENGUJIAN TANPA MERUSAK (NON DESTRUCTIVE TEST) - M. Fahrur Rozy Hentihu; Abdul Hadi Djaelani; Moch. Agus Choiron (ROTOR, 2013)
Elastic modulus of material are usually obtained from tensile test. Tensile test categorized as destructive test. One of destructive test weakness is the testing specimen can not be reused. So we need alternative on elastic modulus test without damaging the specimen (non destructive test). This research aims to determine whether the sound frequency of material can be used as a basic for elastic modulus test as a non destructive test. On this research, two different test performed on the same specimen. First test is testing elastic modulus using sound frequency test (non destructive test) and second test is testing elastic modulus using tensile test (destructive test). Percentage error obtained from comparing percent error between those two tests. The results showed, in testing the elastic modulus of brass specimen has an error percentage of 10.33%, in testing the elastic modulus of aluminium specimen has an error percentage of 4.39%, and in testing the elastic modulus of steel specimen has an error percentage of 1.89%. Keywords: Elastic modulus, Non destructive test, Sound frequency